Efficacy of Pineapple Juice as a Negative Oral Contrast in Magnetic Resonance Cholangiopancreatography - Khadka, Roshana; Pokhrel, Abisekh; Shah, Bhanu Pratap; Bhattarai, Manoj (Nepal Journal of Medical Sciences, 2024)
Introduction: Magnetic Resonance and Cholangiopancreatography (MRCP) is a noninvasive test used in the evaluation of the pancreaticobiliary system. Pineapple juice (PJ) acts as a safe, cheap and readily available effective negative contrast which helps in increasing the conspicuity of the biliary system in MRCP. This study was done to find out the efficacy of pineapple juice as a negative contrast agent on MRCP Methods: A cross-sectional study was conducted in the Department of Radiodiagnosis and Imaging from April 2023 to August 2023.Ethical clearance was taken and all consecutive patients fulfilling the criteria and undergoing MRCP over the study period of 3 months with effect from 8/04/2023 were included in the study. Results: There was a significant improvement in the contrast effect scores between the pre-PJ and 30-minute post-PJ images (p<0.001). Also, there was a significant improvement in the image effect score between the pre and 30-minute post-PJ images for visualization of the CBD and MPD. Conclusions: This study demonstrated that a commercially available and easily consumable quantity of pineapple juice is effective as a negative oral contrast agent and improves the quality of MRCP imaging, specifically improving visualization of the CBD.